2022
DOI: 10.3389/fpubh.2022.950106
|View full text |Cite
|
Sign up to set email alerts
|

Hot topics and frontier evolution in college flipped classrooms based on mapping knowledge domains

Abstract: With the outbreak of COVID-19 and the development of online teaching, the online flipping teaching mode has attracted increasing attention. Systematic analysis of the research status and development trend of the flipped classrooms is significant for guiding the improvement of the quality of online flipped teaching. This study used the metrology software CiteSpace to draw a scientific knowledge map of relevant research in the web of science database from 2013 to 2021. It performed visual analysis of research au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…An author’s contribution to the area of ICT in physiology can be identified by their significant publications and cooperative connections with other authors, which facilitates understanding the progress in ICT in physiology [ 23 ]. Author collaboration appears to be generally limited, and most academic work in this field is conducted in independent teams with minimal cross-team communication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An author’s contribution to the area of ICT in physiology can be identified by their significant publications and cooperative connections with other authors, which facilitates understanding the progress in ICT in physiology [ 23 ]. Author collaboration appears to be generally limited, and most academic work in this field is conducted in independent teams with minimal cross-team communication.…”
Section: Resultsmentioning
confidence: 99%
“…There are currently three main topics generally discussed in the field of ICT: preparation before class, classroom activities, and consolidation after class [ 23 ]. The current hot spots of research in ICT for physiology worldwide focus on active learning, inverted classroom design, student perception and engagement, teaching effectiveness, and teaching evaluation, among others, while the scope of the research includes students, teachers, school teaching management, and national educational guidelines and policies.…”
Section: Discussionmentioning
confidence: 99%
“…The number of papers and their variations represent differences in the amount of research and attention given to the field [21]. Figure 1 shows the published papers related to flipped classroom in CS education during the 17-year period from 2007-2023. ii.…”
Section: Discussionmentioning
confidence: 99%
“…This study maps and analyzes the literature using CiteSpace, a Java application developed by Chaomei Chen's team, where node size, network connectivity, and keyword co-occurrence properties clearly show the current status and trends of research in the field [20]. It can scientifically measure and visualize the literature collections in the field of natural and social sciences, explore the critical paths of disciplinary evolution, and analyze disciplinary themes and trends [21].This study used CiteSpace version 6.2.R3 (64-bit) for the following analysis: i.Statistical analysis: Includes temporal distribution and categorization of publications related to the flipped classroom in CS education.…”
Section: 2analysis Methods and Proceduresmentioning
confidence: 99%
“…With the COVID-19 outbreak in 2020, the idea of "classes suspended but learning continues" is rapidly driving the development of flipped classrooms in the context of various regional containment (Durfee et al, 2020;Wang et al, 2021;Feng et al, 2022). Consequently, the flipped classroom is gaining momentum, and educators from different countries continue contributing to its development and impact (Sun et al, 2022). A randomized controlled trial conducted by American scholars (Paul et al, 2023) showed that the flipped classroom significantly improves the clinical skills of medical students compared to online-only learning.…”
Section: Introductionmentioning
confidence: 99%